Exploring Alternative Designs using ‘Big’ Administrative Data - Leslie Roos; Elizabeth Wall-Wieler; Mahmoud Torabi (International Journal of Population Data Science, 2018)
Introduction Large population-based data sets present similar analytic issues across such fields as: population health, clinical epidemiology, education, justice, and children’s services. Step-wise approaches and generalized tools can bring together several pillars: big (typically administrative) data, programming, and study design/analysis. How can we improve efficiency and explore alternative designs?